Social Media Influence on Development of Carl Casper’s Image in Chef: Frank Jefkin’s Perspective - Rumandang Bulan, Firdaeisyia; Sumayah (Surakarta English and Literature Journal, 2025)
This research analyzes the impact of social media on Carl Casper’s professional image, using Frank Jefkins' Image Theory from Essentials of Public Relations (1988). The study explores how social media shapes Carl’s public perception and career development in the film Chef (2014), directed by Jon Favreau. Utilizing a qualitative approach, the research examines Carl’s transformation through the four stages of Jefkins' theory: Mirror Image, Current Image, Wish Image, and Multiple Image. Data are collected through repeated viewings of the film, analysis of critical scenes, and examination of secondary sources related to social media’s role in shaping Carl’s image. The findings reveal that while social media initially amplifies Carl’s struggles, it ultimately becomes a powerful tool for rebuilding his career. Managed by his son Percy, Carl’s use of social media reshapes his image, turning criticism into admiration and reconnecting him with his audience. This study highlights the transformative potential of digital platforms in public relations and personal branding.